Structure-activity relationships of 4-hydroxy-4-biaryl-proline acylsulfonamide tripeptides: A series of potent NS3 protease inhibitors for the treatment of hepatitis C virus. Issue 3 (1st February 2017) - Wang, Alan Xiangdong; Chen, Jie; Zhao, Qian; Sun, Li-Qiang; Friborg, Jacques; Yu, Fei; Hernandez, Dennis; Good, Andrew C.; Klei, Herbert E.; Rajamani, Ramkumar; Mosure, Kathy; Knipe, Jay O.; et al.
Graphical abstract: Abstract: The design and synthesis of a series of tripeptide acylsulfonamides as potent inhibitors of the HCV NS3/4A serine protease is described. These analogues house a C4 aryl, C4 hydroxy-proline at the S2 position of the tripeptide scaffold. Information relating to structure-activity relationships as well as the pharmacokinetic and cardiovascular profiles of these analogues is provided.